EVALUASI TARIF ANGKUTAN UMUM BERDASARKAN BIAYA OPERASIONAL KENDARAAN (STUDI KASUS ANGKOT KUD TRAYEK BUKITTINGGI - SUNGAI PUA) - Adriyanto Yusuf; Ishak Ishak; Yorizal Putra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Public transportation is used by the public in activities to move goods or people from one place to another. In using public transport services, people pay tariffs according to government. Changes in economy give an impact on public transportation tariffs. Tariffs of public transportation should match the BOK's calculations analysis. The study conducted a calculation analysis of BOK in determined tariffs public transportation of KUD route of Sungai Pua – Bukittinggi. An analysis based on BOK has been obtained there is a discrepancy between tariffs by government and in the field based on BOK. Tariffs that determined by government and in the fields in amount of Rp. 5.000,00 and the result based on BOK, tariffs on Monday about Rp. 4539.94 until Rp. 4.969,02 and Saturday about Rp. 4173,99 until Rp. 4.969,02. It can concluded that the differences between tariffs, determine by government and in the field with tariffs based on BOK calculations about Rp. 271,65 on Monday and Rp. 493,80 on Saturday. The aim of this study are for public transportation entrepreneurs to provide prime services to people who use public transportation and government are expected to issue policies that will increase the interest of public to use public transportation services. Keywords : Tariff Evaluation, Public Transportation, BOK.